Long-term effects of virtual reality-based therapy in cardiovascular rehabilitation: A longitudinal study - Alves da Cruz, Mayara [UNESP]; Laurino, Maria [UNESP]; Christofaro, Diego [UNESP]; Ghisi, Gabriela; Vanderlei, Luiz [UNESP] (Taylor & Francis, 2022)
Background: In Cardiovascular Rehabilitation (CR), patient adherence to the maintenance phase is a major challenge. Virtual reality-based therapy (VRBT) promotes acute hemodynamic and autonomic repercussions similar to traditional rehabilitation and can increase patient adherence to the program. However, it is unknown whether the combination of VRBT to a traditional CR manages to maintain or even improve clinical and autonomic variables in long term. Objective: To analyze whether VRBT combination in a traditional CR can maintain or improve clinical and autonomic variables in cardiac patients in the maintenance phase of these programs. Methods: Twenty-six volunteers (62.04 ± 12.22 years) were evaluated, who underwent an initial assessment and two other assessments (in the sixth and 12th week) of the following outcomes: systolic and diastolic blood pressure, respiratory rate, pulse saturation of oxygen, heart rate, perceived exertion, and cardiac autonomic modulation, using linear and non-linear heart rate variability methods. Results: Except for the apparent lack of clinical significance observed in Shannon Entropy, LF (nu), and HF (nu), the combination of VRBT as routine in a traditional program did not cause significant changes in the analyzed variables. Conclusion: combination of VRBT was able to maintain the chronic hemodynamic and autonomic repercussions caused by traditional CR.
Keywords: autonomic nervous system; Cardiac rehabilitation; cardiovascular diseases; exercise; virtual reality exposure therapy